Legal Awareness Level of Electronic Information and Transaction Law Viewed from Understanding and Legal Attitude Aspects Among Students at SMA Negeri 1 Gianyar - Griyawana, I Wayan Gede; Sidaryanti, Ni Nyoman Asri; Yudana, I Made; Diputra, I Putu Nova; Dewi, Desak Made Putri Pradnyan; Dewi, Desak Nyoman Indah Pradnya; Putra, I Gusti Bagus Satria Pratama (Jurnal Media Komunikasi Pendidikan Pancasila dan Kewarganegaraan, 2026)
The digitalization era has transformed social interactions through social media, particularly among Indonesian youth with 204.7 million internet users. Implementation of the Electronic Information and Transaction Law (UU ITE) faces complex challenges among students as digital natives who exhibit a paradox between high technological capabilities and limited digital legal awareness. This study aims to analyze understanding levels and legal attitudes of students at SMA Negeri 1 Gianyar towards UU ITE and identify factors influencing the "digital legal awareness paradox". A descriptive quantitative method was employed involving 330 students through multiple-choice tests (25 items) to measure understanding and Likert scale questionnaires (25 items) to measure legal attitudes. Analysis focused on four indicators of legal understanding and three indicators of legal attitudes. Results show good understanding levels with an average of 80.36 but high variability (range 52-96), while student attitudes remain neutral at 3.5. Findings reveal a "digital legal awareness paradox" where students understand UU ITE's importance but worry about potential misuse, influenced by developmental psychology characteristics, digital native generation traits, and Social Learning Theory. This research provides important contributions for developing more effective digital legal education strategies.